A STUDY OF COMMUNITY ACCEPTANCE AND THE ROLE OF PHILANTHROPIC ORGANIZATIONS IN THE REINTEGRATION OF FORMER NON-STATE ARMED YOUTH IN THE NIGER DELTA REGION OF NIGERIA - Okechuku Onuchuku; Chibuzor Chile Nwobueze; Kelechi Belinda Udeogu (PT. Antis International Publisher, 2026)
Objective: The transition of former violent non-state actors from the creeks of the Niger Delta back into society remains one of the most volatile challenges in Nigeria’s post-amnesty landscape. This paper examines at how important community acceptance is, and the significant role charities play in getting people back into society. Disarmament, Demobilization and Reintegration (DDR) programmes can be state run with a focus typically on training for work, but not on the social debt and trauma that engendered community opposition. Method: This research using qualitative analysis of host community perceptions demonstrates that reintegration is not a top-down bureaucratic event but a contentious bargain of trust, and the automatic nature of structural stigma is detrimental to social peace. Results: This paper delineates what it sees as a considerable “legitimacy gap” surrounding state interventions that philanthropic organizations are excellently placed to fill. Non-state actors facilitate restorative justice mechanisms that go beyond mere economic settlement. Findings reveal that philanthropic involvement is most effective when it shifts the focus from individual rehabilitation to communal healing, addressing the grievances of victims alongside the needs of former combatants. Novelty: The paper maintains that, before uncertainty is transformed to sustainable peace, security forces must stop regarding armed youth as militants and embrace social acceptability with accountability and trust combined.